Digital Marketing Training in UMKM Kinasih Fish - Zulfikar Muhammad Reza; Inna Setiawati; Triana Apriliyanti; Mandarosi Sofiansori; Ria Arinta Putri (Yayasan Putra Adi Dharma, 2023)
UMKM Kinasih Fish operates in the field of processing eel chips. UMKM Kinasih Fish is located at Rt.10, Piringan, Dk Gumulan, Caturharjo, Pandak, Bantul, DIY. The production scale for eel chips from Kinasih Fish is still relatively small, namely 3-4kg of eel per day. This is because the new marketing relies on entrusting it to grocery stalls and digital marketing via Facebook and WhatsApp status alone, and even that is not very optimal. The training methods used are potential mapping, improving packaging quality, and product marketing through digital media and marketplaces. The results of service activities include mapping the profile of UMKM Kinasih Fish, providing packaging suggestions, overseeing the issuance of business legality (P-IRT), providing training in creating and operating digital media to support product marketing. This service program is expected to increase marketing through digital media so as to increase sales of UMKM Kinasih Fish.